Addressing the Biochemical Foundations of a Glucose-Based "Trojan Horse"-Strategy to Boron Neutron Capture Therapy: From Chemical Synthesis to In Vitro Assessment - Jelena Matović; Juulia Järvinen; Helena C. Bland; Iris K. Sokka; Surachet Imlimthan; Ruth Mateu Ferrando; Kristiina M. Huttunen; Juri Timonen; Sirpa Peräniemi; Olli Aitio; Anu J. Airaksinen; Mirkka Sarparanta; et al. (AMER CHEMICAL SOC, 2022)
Boron neutron capture therapy (BNCT) for cancer is on the rise worldwide due to recent developments of in-hospital neutron accelerators which are expected to revolutionize patient treatments. There is an urgent need for improved boron delivery agents, and herein we have focused on studying the biochemical foundations upon which a successful GLUT1-targeting strategy to BNCT could be based. By combining synthesis and molecular modeling with affinity and cytotoxicity studies, we unravel the mechanisms behind the considerable potential of appropriately designed glucoconjugates as boron delivery agents for BNCT. In addition to addressing the biochemical premises of the approach in detail, we report on a hit glucoconjugate which displays good cytocompatibility, aqueous solubility, high transporter affinity, and, crucially, an exceptional boron delivery capacity in the in vitro assessment thereby pointing toward the significant potential embedded in this approach.